Impact of CAP Subsidies on Profit in Agricultural Enterprises in Slovakia - Marián Tóth (Polityki Europejskie, Finanse i Marketing)
In this article we focus on the evaluation of subsidies and profit. To evaluate the importance of subsidies in relation to income, we selected two indicators. The first is a proportional indicator of profit per hectare of agricultural land and the second is the (profit minus subsidy) per hectare of agricultural land. These indicators enable to assess the status of farms in case that they would not receive subsidies. Chosen time horizon from 1993 to 2008 also allows assessment of the progress of the importance of subsidies in terms of ability to make a profit.